Report of the Third Annual CCAFS Science Workshop Agenda - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The Third Annual CCAFS Science Workshop focused on consolidating research and fostering collaboration across the CGIAR. Day‐1 plenary presentations along four themes identified issues including: • Opportunities to deliver messages to UNFCCC through SBSTA; • The challenges of communicating science; • The multiple scales of climate variability, stakeholder engagement, and adaptation options; • Whether adaptation and mitigation are synergistic or conflicting; • Participation as an opportunity to give respect, voice and choice – without precluding the impact of scientific knowledge. Day‐2 parallel sessions enabled knowledge sharing and planning around topics of strategic interest to CCAFS. Opportunities for cross‐Center follow‐up actions include: • Developing a community of practice and web portal around diversification and climate risk; and projects that use household modeling to design diversification strategies; • Development of a simple, rigorous, consistent protocol for GHG measurement in smallholder agriculture. • A workshop to address results of a scoping study and launch a community of practice on modeling climate impacts on pests and diseases. • Development of a proposal for CCAFS to catalyze new work on gender and Climate‐Smart Agriculture coordinated across centers and CRPs. • Synthesis of knowledge about costs and benefits of Climate‐Smart Agriculture practices; and evidence about what triggers change among smallholder farmers. • A Science magazine article on the concept of Climate‐Smart Agriculture.